Incidental Parathyroidectomy during Total Thyroidectomy: Risk Factors and Consequences. (18th August 2016) - Manatakis, Dimitrios K.; Balalis, Dimitrios; Soulou, Vasiliki N.; Korkolis, Dimitrios P.; Plataniotis, Georgios; Gontikakis, Emmanouil
Abstract : Objective . To evaluate the incidence of accidental parathyroidectomy in our series of total thyroidectomies, to investigate its clinical and biochemical consequences, and to identify potential risk factors. Methods . Patients who underwent total thyroidectomy between January 2006 and December 2015 were retrospectively analyzed. Pathology reports were reviewed to identify those cases who had an incidental parathyroidectomy and these were compared to patients with no parathyroidectomy, in terms of clinical (age, sex, and symptoms of hypocalcemia), pathological (thyroid specimen weight, Hashimoto thyroiditis, and malignancy), and biochemical (serum calcium and phosphate levels) factors. Results . 281 patients underwent total thyroidectomy during the study period. Incidental parathyroidectomy was noticed in 24.9% of cases, with 44.3% of parathyroid glands found in an intrathyroidal location. Evidence of postoperative biochemical hypocalcemia was noticed in 28.6% of patients with parathyroidectomy, compared with 13.3% in the no-parathyroidectomy group (p = 0.003 ). Symptomatic hypocalcemia was observed in 5.7% and 3.8%, respectively (p = 0.49 ). Age, sex, thyroid specimen weight, Hashimoto thyroiditis, and malignancy did not differ significantly between the two groups. Conclusions . Our study found an association of incidental parathyroidectomy with transient postoperative biochemical hypocalcemia, but not with clinically symptomatic disease. Age, sex, thyroid gland weight, Hashimoto thyroiditis, and malignancy were not identified as risk factors.